Analysis of Hydrodynamics of Fluid Flow on Corrugated Sheets of Packing. (26th July 2012) - Subramanian, Kumar; Wozny, Günter
Abstract : Modelling of the hydrodynamics behaviour of the liquid on the corrugated sheets of packing is studied using three-dimensional, volume-of-fluid (VOF) model that is incorporated in Ansys Fluent 12.0. The flow of three different liquids with different physical properties is modelled. A domain of corrugated sheets of packing resembling the real structured packing with little modifications in the elementary geometry is constructed using ICEM CFD 12.0. The quantitative comparisons of the wetting behavior from the simulations are in good agreement with experiments. Further, the study has been extended to understand the influence of the second corrugated sheet on the flow behavior. The contours from the simulations indicate the liquid hold-up in the crimp of two corrugated sheets, and these results are in good agreement with the earlier experimental studies performed using X-ray tomography in the literature. The result from the simulation shows that even for the high flow rate of around 811 mL/min for silicon-oil (DC5), only 60% of the corrugated sheet has been wetted. Hence, the efficiency of the existing packing can be further increased by increasing the wetted area in the corrugated sheet of packing.